Technological progress and (un)employment development - Uwe Blien; Oliver Ludewig (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2016)
One of the key issues in economics is the explanation of unemployment and its variation across different economies. Modern mainstream macroeconomics refers to the effects of financial crises and to institutional structures and their variation across countries. However, unemployment within the European states varies nearly as much as between these countries. In the interior of a country, however, there are only minor differences in institutions. To solve this puzzle, we explain this variation of unemployment building on the regional industry composition and technological progress. It is shown formally that under general and standard preconditions the price elasticity of demand on product markets is decisive: Technological progress leads to an expansion of employment if product demand is elastic. It is accompanied, however, by shrinkage of employment if product demand is inelastic. A transition from the elastic into the inelastic range of the demand function for the most important product(s) can already suffice to plunge a region into crisis. In our empirical analysis we use industry level time series data on output, prices, employment and national income for Germany provided by the Federal Statistical Office. We estimate Marshallian type demand functions using an instrumental variables estimator to derive the price elasticities for different industries and link this information to the regional labour market performance of the respective industries and regions. – – Ein wichtiges Thema der Volkswirtschaftslehre ist die Erklärung der Arbeitslosigkeit und ihrer Variation gemäß unterschiedlicher Bedingungen. Verschiedene moderne Ansätze führen die Höhe der Arbeitslosigkeit auf institutionelle Regelungen der betroffenen Volkswirtschaften zurück. Eine solche Erklärung steht jedoch für die Erklärung der Unterschiede der regionalen Arbeitslosigkeit nicht zur Verfügung, da die Institutionen innerhalb eines Landes weitgehend konstant sind. Um eine Erklärung zu bieten, rekurrieren wir auf die Industriestruktur der Ökonomien und auf den technischen Fortschritt. Unter Verwendung eines formalen Modells wird gezeigt, dass unter sehr allgemeinen Bedingungen die Preiselastizität der Nachfrage auf Produktmärkten entscheidend ist: Technischer Fortschritt führt zu einem Wachstum an Beschäftigung, wenn die Nachfrage elastisch reagiert. Ist die Nachfrage hingegen inelastisch, führt technischer Fortschritt zu einer Reduzierung der Beschäftigung. In der empirischen Analyse verwenden wir Industriedaten, um zunächst die Preiselastizität der Nachfrage in einem Modell mit Instrumentalvariablen abzuschätzen. Im folgenden Schritt analysieren wir die Nachfrage nach Arbeit in Abhängigkeit von der Preiselastizität auf dem Gütermarkt und vom technischen Fortschritt.
Keywords: Q33; R11; J23; 330; Structural change; Productivity growth; Labour market dynamics